Phenotypic Performance of Kanesia-10 Cotton (Gossypium hirsutum L.) Variety Through the Use of Liquid Organic Fertilizers in Low Land - Mayasari Yamin; Rahman Hairuddin; Nining Triani Thamrin; Eka Suddartik (Universitas Sembilanbelas November Kolaka, 2019)
The program of cotton variety improvement is carried out by increasing the productivity and quality of fiber in order to rise the competitiveness of cotton farming through the production of fiber quality that is in accordance with the demand of export-oriented national textile industry. This study aimed to determine the performance of the Kanesia-10 cotton phenotype cultivated using liquid organic fertilizer in the lowlands and obtain the best concentration of liquid organic fertilizer in improving Kanesia 10 cotton performance. This research was conducted in Experimental Farm of the Faculty of Agriculture of the University of Cokroaminoto Palopo from August to November 2018. The genetic material used was Kanesia 10 cotton variety for its fiber content of 27.2%, production of 2.457,2 kg cotton seed per hectare and fiber uniformity of 83,3-84,6%. This study used a randomized block design consisting of five treatments and four times. The treatment used was control (P0), 50 ml/L POC of gamal leaves (P1), and 100 ml/L of gamal leaves (P2) 150 ml/L POC of gamal leaves (P3), and 200 ml/L POC of gamal leaves (P4), so that there were 20 experimental units. The use of liquid organic fertilizer produces heterogeneous phenotypic performance for the parameters of the number of fruits per plot with a diversity coefficient value reaching 32.93%. The treatment of liquid organic fertilizer with a concentration of 50 ml / L resulted in the performance of plant height, number of leaves, number of fruits per plot, and the best fruit weight per plot with a mean of 64.13 cm, 57.75 strands, 43.00 fruits and 7.60 g, respectively